AWS certified solutions architect study guide : Associate (SAA-C01) exam - Piper, Ben (Sybex, 2019)
"The AWS certified solution architect associate certification gives you a definite advantage in the competitive market for cloud specialists. For the new, revised Associate exam SAA-C01, this comprehensive, fully updated study guide is indispensible. It covers all relevant aspects of the job role, including mapping multi-tier architectures to AWS services, loose coupling and stateless systems, applying AWS security features, deploying and managing services, designing large scale distributed systems, and much more. Everything you need to know is here, along with practice questions and chapter reviews. Add the exclusive Sybex interactive online test bank and learning environment, and you can approach test day with confidence."--Provided by publisher...
Includes index